EFFICACY OF EARLY-ONSET SEPSIS CALCULATOR IN THE PREDICTION OF ANTIBIOTICS USAGE AMONG NEONATES: A LOCAL SETTING STUDY - HABIB , M (Biological and Clinical Sciences Research Journal, 2024)
Early-onset sepsis (EOS) in neonates is a critical condition that requires timely diagnosis and appropriate management to prevent adverse outcomes. However, overuse of antibiotics in neonates can lead to complications, including antimicrobial resistance. The EOS calculator is a clinical tool designed to assess the risk of sepsis in neonates, helping to guide antibiotic use. Its efficacy in predicting antibiotic administration in high-risk neonates needs further evaluation. Objective: To evaluate the efficacy of the EOS calculator in predicting the use of antibiotics in neonates admitted to the neonatal intensive care unit (NICU) at a tertiary care hospital. Methods: This comparative cross-sectional study was conducted in the Pediatrics Department of Combined Military Hospital, Peshawar, from August 2020 to June 2022. A total of 982 neonates admitted to the NICU due to a high risk of infection were included. Upon admission, the attending clinician applied the EOS calculator to each neonate. However, the results were kept confidential, and routine management, including antibiotic administration, was carried out based on clinical signs and relevant investigations. The use of antibiotics within 72 hours of admission was compared to the recommendations of the EOS calculator. Statistical analysis used chi-square tests to assess the association between antibiotic use and the EOS calculator's recommendations. Results: Out of the 982 neonates included, 590 (60.1%) were male, and 392 (39.9%) were female, with a mean age of 1.38±4.53 days. Within 72 hours of admission, 562 (57.2%) neonates did not receive antibiotics according to local protocols. A statistically significant association was observed between the clinical use of antibiotics and the recommendations of the EOS calculator (p-value <0.001), demonstrating that the calculator could effectively predict antibiotic needs. Conclusion: The EOS calculator proved to be an effective tool in predicting the likelihood of sepsis in neonates at high risk of infection. Its use can guide clinicians in making informed decisions about antibiotic administration, reducing unnecessary antibiotic exposure while ensuring timely treatment for those who need it. Incorporating the EOS calculator into neonatal sepsis management protocols can enhance patient outcomes and help prevent the overuse of antibiotics in neonates.